1989
DOI: 10.1007/bf02385434
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization studies of ZrO2−SiO2 composite gels

Abstract: Composite ZrO2-SiO2 powders were prepared using a gel route. Morphological and crystallographic features of ZrO 2 particles formed during the heat treatment, and the particle sizes of the composites have been investigated. The following polymorphic changes have been observed during the heat treatment: amorphous -+ metastable-cubic/tetragonal ZrO 2 --~ tetragonal ZrO2 ~ monoclinic ZrO2. SiO2 crystallizes above 1273 K. The martensitic transformation of Zr02 (t -, m) was observed in situ, when exposed to a high-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
1

Year Published

1994
1994
2007
2007

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 88 publications
(45 citation statements)
references
References 9 publications
(11 reference statements)
1
43
1
Order By: Relevance
“…At approximately 12003C, both phases react to form zircon, the excess ZrO remaining monoclinic. In general, increases in silica content in the compositions used in the present study improves the thermal stability of Z(t), which is corroborated in other studies (16,21). The upper stability limit of the tetragonal phase varied between 850 and 12003C, depending on the ZrO /SiO ratio.…”
Section: For the 40zrosupporting
confidence: 90%
See 3 more Smart Citations
“…At approximately 12003C, both phases react to form zircon, the excess ZrO remaining monoclinic. In general, increases in silica content in the compositions used in the present study improves the thermal stability of Z(t), which is corroborated in other studies (16,21). The upper stability limit of the tetragonal phase varied between 850 and 12003C, depending on the ZrO /SiO ratio.…”
Section: For the 40zrosupporting
confidence: 90%
“…This is due to the formation of microcrystalline zirconia and to preparation conditions (4, 37}39). When nanocrystalline nondoped zirconia is annealed, the tetragonal phase is transformed into the monoclinic phase (40,41), a transformation that begins at approximately 4503C (24) and can be completed between 800 and 10003C (19,21,30). In the present study, however, the formation of Z(t) was detected with XRD as beginning in the earliest stages of thermal treatment (1503C).…”
Section: Resultscontrasting
confidence: 60%
See 2 more Smart Citations
“…[45] This phenomenon, which occurs whenever zirconia or hafnia are homogeneously dispersed in a silica matrix, has been extensively described in the literature. [7,[54][55][56][57][58][59][60][61][62] Generally, the crystallization of tetragonal zirconia has been reported to occur after calcination at 400°C, [15] while partial transformation from tetragonal to monoclinic was reported to occur at 800-900°C and the single monoclinic phase is present at temperatures higher than 1000-1200°C. However, Neumayer and Cartier [15] reported that the addition of silica to zirconium and hafnium oxide was found to increase the temperature of crystallization of zirconium oxide, to stabilize the formation of tetragonal hafnia, and to increase the temperature at which the transformation of ZrO 2 or HfO 2 from the tetragonal to the monoclinic phase occurs.…”
Section: Full Papermentioning
confidence: 99%